Uso de canciones en educación media para la enseñanza del idioma inglés en Tegucigalpa, Honduras - Obando, Katya Alejandra Mejía (Universidade Federal de São Carlos, 2016)
The following research was carried out in Tegucigalpa, Honduras, specifically at high school level in public schools. The objective of this research is to know, through surveys, the teachers´ and students’ perceptions, about the use of songs in English teaching. This research is divided into three chapters the first called educational stage of Honduras, in which the its describe the location of the Central American country, as well as a brief description of the economic and social situation of the country. In addition, it describes how the education system in Honduras is organized based on the National Basic Curriculum (CNB), also defines the purpose of each educational level, with an emphasis on the high school level. The second chapter is about the English teaching methodology, and the relevance in Honduras. It also explains the proper use of English songs to increase the four basic skills of a language (listening, speaking, reading and writing). The third and final chapter shows the data analysis about the surveys applied in high school level to teachers and students. At the end of the third chapter it is suggested a didactic proposal based on the songs mentioned by teachers and students.
Keywords: Honduras; Educación media; Canciones; Enseñanza del idioma inglés; High school; Songs; Teaching english as foreign language; CIENCIAS HUMANAS::EDUCACAO